Impact of Laparoscopic Sleeve Gastrectomy on Thrombomodulin Concentration and Early Markers of Atherosclerosis - Hasan Elkan; Mehmet Memduh Baş; Berna Kaya (Journal of Interventional Cardiology)
Background. Thrombomodulin, an integral membrane protein functioning as a cofactor in the anticoagulant pathways, has recently emerged as a marker of endothelial dysfunction. This study aimed to investigate the impact of laparoscopic sleeve gastrectomy (LSG) on thrombomodulin concentration and early markers of atherosclerosis. Methods. Forty-four subjects undergoing LSG were prospectively examined. The change in thrombomodulin concentration from baseline (preoperative) to the sixth postoperative month following the LSG and the relationship between the change in thrombomodulin concentration and BMI, CIMT, ABI, and blood lipids were examined. Results. The medical records were available for 44 patients (mean age: 37.2 ± 10.9 years, 65.9% male). LSG led to significant reductions in total body weight and body mass index (BMI) at postoperative six months (37.0 ± 5.6 kg/m2 vs. 47.1 ± 5.8 kg/m2, p<0.001). Markers of early atherosclerotic events, including carotid intima-media thickness (CIMT) and ABI, improved. The change in thrombomodulin concentration (Δ TMD) was significantly correlated with the change in Δ BMI (r = 0.500, p=0.011), Δ LDL (r = 0.389, p=0.032), Δ systolic blood pressure (r = 0.384, p=0.012), and Δ CIMT (r = 0.327, p=0.012) and was negatively correlated with Δ HDL (r = −0.344, p=0.020) and Δ ABI (r = −0.357, p=0.020). Conclusion. LSG leads to significant improvements in blood lipids, systolic and diastolic blood pressure, and in surrogate markers of atherosclerotic burden and endothelial function, including thrombomodulin, ABI, and CIMT, at postoperative six months. LSG might prevent or reduce atherogenesis in the early stages by stopping endothelial dysfunction.